2001
DOI: 10.1007/bf02693794
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for carotid artery stenosis following neck irradiation

Abstract: Carotid angioplasty and stenting (CAS) is being promoted for patients with carotid artery stenosis who have received neck irradiation. We reviewed our experience with carotid endarterectomy (CEA) following neck irradiation to determine if indeed postoperative and long-term problems were an issue in these patients. Over the past 13 years, 10 patients with a history of neck irradiation underwent 11 procedures. The average time interval between radiation treatment and surgery was 14 years (range 1-44). All caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“…36,37 In total 2 patients developed an ipsilateral occlusion. 9,37 Comparison of outcomes for restenosis and/or occlusion showed a significant difference favoring CEA (Pϭ0.003).…”
Section: Restenosismentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 In total 2 patients developed an ipsilateral occlusion. 9,37 Comparison of outcomes for restenosis and/or occlusion showed a significant difference favoring CEA (Pϭ0.003).…”
Section: Restenosismentioning
confidence: 99%
“…35 Six studies reporting on this specific end point did not encounter any nerve problems at all. 9,18,34,38,40,41 Other procedure-specific complications were incidental, including wound infection and bleeding needing reintervention (Table 4). 21,34,36,37 Late Outcome…”
Section: Early Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies are retrospective surgical case series on patients with extracranial carotid stenosis and favor either stenting [67][68][69][70][71] or endarterectomy. 14,[72][73][74][75] Neither approach is clearly superior, as no prospective head-to-head trial exists. A 3-year prospective study has suggested that postangioplasty restenosis rates are significantly higher than proposed.…”
Section: Managementmentioning
confidence: 99%
“…In lieu of performing standard carotid endarterectomy (CEA), which may increase the risk of operative complications, carotid artery stenting (CAS) has been suggested in these patients as a minimally invasive alternative. [6] The purpose of this retrospective study was to investigate the effect of neck XRT on the long-term outcome of patients undergoing CAS.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%